2020
DOI: 10.1101/2020.04.13.20064287
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Does TB Vaccination Reduce COVID-19 Infection? No Evidence from a Regression Discontinuity Analysis

Abstract: In the middle of the global COVID-19 pandemic, the BCG hypothesis, the prevalence and severity of the COVID-19 outbreak seems to be correlated with whether a country has a universal coverage of Bacillus-Calmette-Guérin (BCG), a vaccine for tuberculosis disease (TB), has emerged and attracted the attention of scientific community and media outlets. However, all existing claims are based on cross-country correlations that do not exclude the possibility of spurious correlation. We merged country-age-level case st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 9 publications
0
10
0
2
Order By: Relevance
“…While some of the previous studies have observed associations between BCG vaccination policy and spread of COVID-19 (Miller et al, 2020; Berg et al, 2020), others criticized their work and showed that after corrections for various covariate factors, no statistically significant associations could be found Hensel et al (2020); Fukui et al (2020); Singh (2020). Most of these studies have used indicators that were quite straightforward, such as the number of reported cases per million inhabitants on a particular date.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While some of the previous studies have observed associations between BCG vaccination policy and spread of COVID-19 (Miller et al, 2020; Berg et al, 2020), others criticized their work and showed that after corrections for various covariate factors, no statistically significant associations could be found Hensel et al (2020); Fukui et al (2020); Singh (2020). Most of these studies have used indicators that were quite straightforward, such as the number of reported cases per million inhabitants on a particular date.…”
Section: Discussionmentioning
confidence: 99%
“…The associations between BCG vaccination policy and COVID-19 disease progression have also been a subject to controversy in data analysis, with some studies claiming significant effects on the number of cases and case fatality rates (Miller et al, 2020; Berg et al, 2020), while others criticizing weaknesses of those studies and claiming no statistically significant differences (Szigeti et al, 2020; Hensel et al, 2020; Fukui et al, 2020; Singh, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…To construct this variable, we initially attributed a value of zero to countries that have never had public vaccination policy for BCG (examples: USA and Italy) 12 . Next, for countries that have an active vaccination program (Brazil and China), the historical average percentage of BCG coverage was used 13 .…”
Section: Bcg Vaccine Immunizationmentioning
confidence: 99%
“…It led to approximately 281 thousand immune people died. Subtracting this number from 12 http://www.bcgatlas.org. 13 https://www.who.int/data/gho/indicator-metadata-registry/imr-details/2442.…”
Section: Bcg Vaccine Immunizationmentioning
confidence: 99%
“…Some advocated that BCG-vaccinated people are less suffered from the virus because COVID-19 high burden countries such as Italy, Spain, USA, and France do not currently recommend universal BCG vaccination [ 2 3 4 ]. However, the others objected because this seemingly attractive relationship is explainable with confounding factors such as aged society, resource rich medical system to detect COVID-19, lower temperature, and advanced reporting system of COVID-19 high-burden tuberculosis (TB) low-burden countries [ 5 6 ]. We assessed if country-level universal BCG vaccination policy was associated with decreased mortality from COVID-19 after adjusting multiple possible confounding factors.…”
mentioning
confidence: 99%